Preparation of Chitosan Films and microspheres by Cross-Linking reaction using de-proteinated Epoxidized natural rubber for skin drug delivery - Surakarn Paichamnan (Prince of Songkla University, 2016)
Thesis (Ph.D., (Pharmaceutical Sciences))--Prince of Songkla University, 2014